(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
General studies on individualized pattern making were reviewed. A computerized method of designing high-value-added apparel was developed using three-dimensional data for an individual. In our system, the grainline and cutting line were set taking into account the shear limit angle of the cloth material. Skirts, pants and upper garments with sleeves were made using our system. Individualized clothes were successfully made using our program.